ENVELHECIMENTO ARTIFICIAL ACELERADO POR RADIAÇÃO ULTRAVIOLETA DE MADEIRAS DE Eucalyptus benthamii E Pinus caribaea var. hondurensis - Martins, Sabrina Andrade; Santos, Cristiane Moreira Tavares dos; Gonçalez, Joaquim Carlos; Camargos, José Arlete Alves (Floresta, 2011)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Este trabalho teve como objetivo avaliar os processos de fotodegradação da cor superficial de duas espécies de madeiras, Pinus caribaea var. hondurensis e Eucalyptus benthamii, ao longo do tempo de exposição à radiação ultravioleta em um reator fotoquímico. As amostras de P. caribaea var. hondurensis foram avaliadas na face radial, enquanto que as de Eucalyptus benthamii na face tangencial. As medidas dos parâmetros colorimétricos, segundo o Sistema CIELAB 1976 (L*, a*, b*, C, e h*), foram obtidas por meio de um espectrofotocolorímetro, em intervalos de tempo de 0, 42, 84, 126 e 168 horas. Ambas as espécies apresentaram um escurecimento ao longo do tempo, principalmente nas primeiras horas de exposição. A madeira de E. benthamii apresentou uma maior variação de cor (DE = 19,72) que a madeira de P. caribaea var. hondurensis (DE = 17,82) após as 168 horas. Palavras-chave: Envelhecimento acelerado; colorimetria; madeira; eucalipto; pínus. Abstract Accelerated artificial aging by ultraviolet irradiation of Eucalyptus benthamiiandPinus caribaeavar.hondurensis woods. The main objective of this research was to study the photo degradation process of superficial color of two wood species, Pinus caribaea var. hondurensis and Eucalyptus benthamii, over ultraviolet irradiation exposure time in a photochemical reactor. Pinus caribaea var. hondurensis samples were evaluated in the radial plane, while Eucalyptus benthamii samples were in tangential plane. The colorimetric parameters measures under the CIELAB 1976 system (L*, a*, b*, C, e h*) were obtained using a Spectophotometer, in the following time intervals: 0, 42, 84, 126 and 168 hours. Both species presented darkening over time, especially in the first hours of exposure. The E. benthamii wood had more changes in its color parameters (DE=19.72) than P. caribaea var. hondurensis wood (DE=17.82) after 168 hours. Keywords: Accelerated aging; colorimetry; wood; eucalyptus; pine.